“And We Are Homesick Still”:: Home, the Unhomely, and the Everyday in Anne Wilkinson - Mezei, Kathy (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2005)
Critical attention has been given to the natural and metaphysical elements of Anne Wilkinson's poetry, but the significance of the home and images of everyday life have been ignored. Although it is often obscured, the domestic plays a vital role in the unfolding of Wilkinson's poetics and modernity. Tension between the domestic and the mythic constitutes an ongoing philosophical and poetic inquiry in her works; Wilkinson juxtaposes the decorative and the monumental in an attempt to grapple with modernist conceptions of reality. Her diction and contradictory images alter the reader's understanding of the everyday to involve the intangible and metaphysical. Wilkinson's use of house and home imagery is not intended to domesticate, but to map out a topography of memory, imagination, and the location of the self.